Polystyrene microplastics exposition on human placental explants induces time-dependent cytotoxicity, oxidative stress and metabolic alterations - Ashelley Kettyllem Alves de Sousa; Keyla Silva Nobre Pires; Isadora Hart Cavalcante; Iasmin Cristina Lira Cavalcante; Julia Domingues Santos; Maiara Ingrid Cavalcante Queiroz; Ana Catarina Rezende Leite; Alessandre Carmo Crispim; Edmilson Rodrigues da Rocha Junior; Thiago Mendonça Aquino; Rodrigo Barbano Weingrill; Johann Urschitz; et al. (Frontiers in Endocrinology)
IntroductionMicroplastics (MPs) are environmental pollutants that pose potential risks to living organisms. MPs have been shown to accumulate in human organs, including the placenta. In this study, we investigated the biochemical impact of 5 μm polystyrene microplastics (PS-MPs) on term placental chorionic villi explants, focusing on cytotoxicity, oxidative stress, metabolic changes, and the potential for MPs to cross the placental barrier.MethodsTerm placental chorionic explants were cultured for 24 hours with varying concentrations of PS-MPs, with MTT assays used to determine the appropriate concentration for further analysis. Cytotoxicity was assessed using the lactate dehydrogenase (LDH) release assay over a period of up to 72 hours. Reactive oxygen species formation and antioxidant activity were evaluated using biochemical assays. Metabolomic profiling was performed using proton nuclear magnetic resonance (1H NMR).ResultsPlacental explants exposed to 100 μg/mL of PS-MPs showed a significant increase in cytotoxicity over time (p < 0.01). Levels of mitochondrial and total superoxide anion (p < 0.01 and p < 0.05, respectively) and hydrogen peroxide (p < 0.001) were significantly elevated. PS-MP exposure resulted in a reduction in total sulfhydryl content (p < 0.05) and the activities of antioxidant enzymes superoxide dismutase (p < 0.01) and catalase (p < 0.05), while glutathione peroxidase activity increased (p < 0.05), and the oxidized/reduced glutathione ratio decreased (p < 0.05). Markers of oxidative damage, such as malondialdehyde and carbonylated proteins, also increased significantly (p < 0.001 and p < 0.01, respectively), confirming oxidative stress. Metabolomic analysis revealed significant differences between control and PS-MP-exposed groups, with reduced levels of alanine, formate, glutaric acid, and maltotriose after PS-MP exposure.DiscussionThis study demonstrates that high concentrations of PS-MPs induce time-dependent cytotoxicity, oxidative stress, and alterations in the TCA cycle, as well as in folate, amino acid, and energy metabolism. These findings highlight the need for further research to clarify the full impact of MP contamination on pregnancy and its implications for future generations.